Life safety risk-based requirements for concrete structures in accidental situations caused by gas explosions. (January 2019) - Hingorani, Ramon; Tanner, Peter; Zanuy, Carlos
Highlights: Development of models for estimating structure-related risks due to gas explosions. Establishment of the reliability of RC members designed to current best practice. Deduction of a consequence model for quantification of loss of life. Inference of consequence-dependent target reliabilities for structural members. Abstract: Accidental hazards are associated with large uncertainties regarding their occurrence probability, their effects on a structure and the possible consequences these effects might entail in case of failure. Consequently, decision-making related to safety accounting for such hazards is difficult and prone to be based on irrational grounds. Gas explosions in buildings are a good example therefore. Although dealt with in many codes, they are seldom accounted for in design of building structures. As a consequence, the associated risks are often ignored or sometimes consciously accepted. If this is a justified practice cannot be easily judged however, since under the implicit approach adopted in practice for assuring structural safety the risks are not quantified nor are the acceptable risk levels established. On this background, the paper explores methods and tools for the practical application of explicit risk analysis in connection with the effects of gas explosions on RC structures. A procedure is established to determine structure-related risks to persons and applied to a representative set of structures designed according to current best practice. Target reliabilities for the design of key elements are deduced from the findings. Such target values facilitate rational decisions on both, the need and the appropriate choice of risk-reduction measures to counteract the effects of gas explosions in buildings.